Kaempferol reduces K63-linked polyubiquitination to inhibit nuclear factor-κB and inflammatory responses in acute lung injury in mice. (15th May 2019) - Qian, Jianchang; Chen, Xuemei; Chen, Xiaojun; Sun, Chuchu; Jiang, Yuchen; Qian, Yuanyuan; Zhang, Yali; Khan, Zia; Zhou, Jianmin; Liang, Guang; Zheng, Chao
Highlights: KPF inhibits LPS-induced inflammatory response by modulating NFκB signaling pathway. KPF effectively suppresses IL-1β-activated NF-κB signaling events mechanistically through reducing polyubiquitination on TLR4 pathway. KPF significantly extends the survival of LPS-challenged mice and alleviates ALI by blocking K63-linked polyubiquitination in lung tissue. KPF-responsive pathways may be an excellent target to pursue for the development of therapies for ALI. Abstract: Acute lung injury (ALI) and its severe form, acute respiratory distress syndrome (ARDS), pose a major clinical challenge. The major driving force in this syndrome is pulmonary inflammation. Recent studies have shown that the naturally occurring flavonoid kaempferol (KPF) reduces endotoxin-induced inflammatory responses in mice. However, the mechanisms of these anti-inflammatory activities are not currently known. Here, we show that enhanced inflammatory cytokine production in response to lipopolysaccharide (LPS) is due to increased TGF-β-activated kinase-1 (TAK1) phosphorylation with subsequent activation of nuclear factor-κB (NF-κB). KPF attenuates LPS-mediated production of cytokines as well as activation of NF-κB. Furthermore, we identified that KPF prevents increased K63-linked polyubiquitination on TNF receptor associated factor-6 (TRAF6) and interleukin-1 receptor-associated kinase 1 (IRAK1). K63-linked polyubiquitination is a signal leading to enhanced activation of downstream pathways including TAK1. Our study shows that KPF is effective in reducing lung damage induced by LPS by modulating TRAF6 polyubiquitination. Furthermore, our findings may provide novel molecular targets to alleviate acute lung injury.